Anesthesia and pain management of a patient with Kleefstra Syndrome for robotic ureteral reimplantation. - E. D. Van Der Zwaag; N. A. Bohannon; S. L. Thompson; J. K. Goeller (Pediatric Anesthesia and Critical Care Journal, 2023)
Kleefstra syndrome (KS) is a genetic disorder caused by a microdeletion in the 9q34.3 chromosome with related clinical conditions requiring surgical intervention and careful consideration for anesthetic management includ- ing potential difficult airway, cardiac and neurological considerations, pulmonary infections, reflux and delayed gastric emptying, genitourinary abnormalities, hypoto- nia, and seizure disorders. In addition, we observed unique perioperative pain control considerations. We pre- sent a clinical case involving a 2-year-old female who re- ceived anesthesia for robotic ureteral reimplantation sur- gery. Perioperative implications are discussed and con- siderations for anesthetic care provided.